Perioperative genitourinary infection associated with sodium-glucose co-transporter 2 inhibitor use - Stephen Melnick; Priya Rajagopalan; Theresa Lynn; Anthony Donato (Greater Baltimore Medical Center, 2018)
Context: Sodium-glucose co-transporter 2 (SGLT-2) inhibitors are a novel treatment approved for type 2 diabetes mellitus to lower hyperglycemia, systolic blood pressure, and promote weight loss. Commonly reported serious adverse events include increased mycotic urogenital infections, orthostatic hypotension, and normoglycemic ketoacidosis. Case report: We present a case of a 47-year old man with a history of type 2 diabetes mellitus initiated on the SGLT-2 inhibitor canagliflozin preoperatively before a penile implant, who presented with late postoperative MRSA bacteremia and scrotal abscess requiring implant extraction. Conclusion: As the SGLT-2 inhibitors are gaining in popularity, prescribers must be aware of the potential adverse genitourinary infectious outcomes. Providers should use caution and avoid initiating SGLT-2 inhibitors in the perioperative setting, and may even consider holding or discontinuing this medication in the setting of impending GU surgery.